OP25 Utilising electronic health records to prioritise patients receiving venesection for haemochromatosis following the COVID-19 pandemic. (20th September 2022) - Driver, Robert; Orange, Dawn
Abstract : Introduction: During the COVID-19 pandemic, many elective services were discontinued, including day-case venesection for patients with haemochromatosis. As services resumed, prioritisation of patients for venesection was required according to clinical need. Venesection procedure codes are recorded within inpatient episodes in the hospital electronic health record (EHR). This study aimed to use analysis of these episodes to stratify patients requiring the most urgent venesection. Methods: Utilising a database of 540 patients with haemochromatosis, details of all inpatient episodes between January 2015 and March 2020 were obtained from the hospital's Informatics Department. For each patient, the total number of venesections for each calendar year was obtained, along with the start date of venesection and the hospital site. Patients with cirrhosis were identified from analysis of diagnosis codes contained within the EHR. Those patients with the highest intensity venesection prior to the discontinuation of services, and those who had commenced venesection most recently, were considered the highest priority for venesection. Results: Between January and March 2020, 31 patients had started venesection for haemochromatosis. Among the 540 patients receiving treatment, those undergoing the most intense venesection included 29 patients who had more than 16 procedures in 2019 and 2020. A further 20 patients had received 12–15 venesection and 54 had undergone 8–11 procedures during this period. Patients were stratified according to their local treatment site and venesection was restarted according to clinical need identified by this analysis. Conclusions: Analysis of EHRs has been used extensively in epidemiological research and various methodologies have been developed. This study demonstrates its utility in service development with a direct impact on patient care. This analysis enabled a rapid framework for identifying clinical need, prior to restarting routine monitoring with serum ferritin. Since venesection for haemochromatosis requires a day case admission, these episodes are captured nationally in the Hospital Episode Statistics (HES) database. This study also demonstrates the use of EHRs for future studies in patients with haemochromatosis, including the prevalence of cirrhosis and its complications, analysis of regional variation in service provision, and clinical outcomes.